FOSTERING CULTURAL AWARENESS THROUGH LOCAL HISTORY LEARNING: URANG BANJAR'S TRADITIONAL ECO-FRIENDLY COSMETICS - Mardiani, Fitri; Subroto, Wisnu; Nadilla, Dewicca Fatma; Ameliasari, Neli; Maulani, M. Rifky (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
History learning has the responsibility of passing on culture in the era of globalization and the rapid development of science and technology. Through understanding and appreciation of local traditions, arts, and cultural values, Indonesia's young generation can become proud successors. The purpose of this research is to analyze the implementation of local history learning based on Urang Banjar environmentally friendly cosmetics at SMAN 2 Banjarmasin. The method used is descriptive qualitative. The results obtained are to foster a sense of cultural awareness in students, history teachers try to implement local history learning based on the Bapupur Basah tradition among the younger generation. The students of class X 4 of SMAN 2 Banjarmasin conducted a field research project studying the beauty tradition and the use of Urang Banjar natural cosmetics. In actualization, students not only learn local history, but also develop research skills, collaboration, and presentation of material that can certainly strengthen a sense of cultural awareness and strengthen national identity in the face of changing times.